AKUNTANSI SYARIAH SEBAGAI REFLEKSI AKUNTANSI KONVENSIOANAL - Lusiana Kanji; Gagaring Pagalung; Amiruddin Amiruddin (Jurnal Mirai Management, 2020)
The presence of the Islamic economy is the momentum of changing economic paradigms in Indonesia, Islamic accounting began to show its existence after the flow: socialism, capitalism, fascism and communism are considered to be failures. During this time the process of education which was originally based on Islam has been replaced by the process of western securalism. Muslims now believe that the solution to the problem is to return to Islam as a regulator of the life of Allah, including accounting. The purpose of sharia accounting is the realization of the ultimate love of Allah, by carrying out accountability of submission and creativity, as well as transactions, economic events and production processes within the organization, the delivery of information of a material, mental and spiritual nature, in accordance with Islamic values and Shariah objectives Keywords: Islamic Accounting, Conventional Accounting